Implementasi model pembelajaran berdiferensiasi untuk meningkatkan hasil belajar siswa madrasah ibtidaiyah - Hamid, Ahmad Dhani (Maliki Interdisciplinary Journal, 2025)
Differentiated instruction has become a key strategy in implementing the Independent Curriculum, especially in Islamic elementary schools. This model allows teachers to tailor learning methods to students’ needs, interests, and learning styles. This study aims to describe the implementation of differentiated instruction within the PGMI context and its impact on students’ academic achievement. Using a literature review approach, this article analyzes scholarly sources from the past ten years that are relevant to Islamic primary education practices. The results show that differentiated learning enhances student engagement, motivation, and academic performance, particularly when supported by careful planning and continuous teacher training.